2003
DOI: 10.1203/01.pdr.0000088068.82225.96
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Glucose Metabolism and Early EEG/aEEG in Term Newborn Infants with Hypoxic-Ischemic Encephalopathy

Abstract: The objective was to investigate how early electrocortical background pattern, as recorded with amplitude integrated EEG (aEEG), correlates with global and regional cerebral glucose metabolism (CMRgl) measured by positron emission tomography during the subacute phase after birth asphyxia. Nineteen term infants with hypoxic-ischemic encephalopathy were investigated. The aEEG background was evaluated at 0 -6, 6 -12, 12-24, 24 -48, and 48 -72 h postnatal age, and classified into four categories according to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 34 publications
2
13
0
1
Order By: Relevance
“…The internal trigger for SWC is located in the brainstem and the presence of SWC in healthy term newborns is considered a sign of brain stem integrity [17,18] . In newborns with hypoxic-ischaemic encephalopathy, sleep organization can be altered and the presence of SWC on aEEG is considered to be a good prognostic sign [19] . Timing of onset of SWC has been shown to predict neurodevelopmental outcome [20] .…”
mentioning
confidence: 99%
“…The internal trigger for SWC is located in the brainstem and the presence of SWC in healthy term newborns is considered a sign of brain stem integrity [17,18] . In newborns with hypoxic-ischaemic encephalopathy, sleep organization can be altered and the presence of SWC on aEEG is considered to be a good prognostic sign [19] . Timing of onset of SWC has been shown to predict neurodevelopmental outcome [20] .…”
mentioning
confidence: 99%
“…Functional imaging, which assesses the biochemical alterations in neonatal hypoxic-ischemia, has been reported (10)(11)(12). These studies showed that hypoperfusion changes in specific areas correlated with the perirolandic lesions in children with neonatal asphyxia (10) and that cerebral glucose metabolism measured 8-12 days after asphyxia was highly correlated with the severity of hypoxic-ischemia (12).…”
Section: Discussionmentioning
confidence: 97%
“…Although conventional MRI is accurate and reproducible to show brain lesions in the first 3-4 days after birth, T1-and T2-weighted MRI may appear normal during the first 24 hrs after hypoxic-ischemia (1,8). Functional imaging, such as cerebral perfusion (10,11) and cerebral glucose metabolism (12), has been used to assess biochemical alterations in neonatal brain during the subacute and chronic stages after hypoxic-ischemia. An imaging agent that demonstrates increased uptake and retention in the damaged areas early after hypoxic-ischemia would be very valuable to identify the high-risk newborns for neuroprotective treatment.…”
mentioning
confidence: 99%
“…Abnormal aEEG is also associated with reduced oxygen consumption in the presence of high cerebral oxygen saturations (e.g., low fractional oxygen extraction) in afterbirth asphyxia [ 45 ]. Thorngren-Jerneck et al showed that abnormal aEEG patterns after neonatal H-I were associated with decreased glucose utilization as measured by positron emission tomography, while normal aEEG patterns were associated with normal glucose utilization [ 54 ]. Cooling is frequently instituted as a means of reducing the likelihood of long-term injury in infants who experience hypoxia-ischemia.…”
Section: Eeg and Amplitude-integrated Eeg (Aeeg)mentioning
confidence: 99%